Bernard Shaw's The Black girl in search of God : the story behind the story - Hugo, Leon (Florida Bernard Shaw series., 2003)
''Leon Hugo, a distinguished Shaw scholar from the country in which The Black Girl in Search of God is set, is the ideal critic to examine Shaw's most famous prose tale--an allegory on a par with Voltaire's Candide.''--Stanley Weintraub, Pennsylvania State University''An astute reading of the text.